Precautionary Saving and the Timing of Taxes - Kimball, Miles S.; Mankiw, N. Gregory (Journal of Political Economy, 1989)
This paper analyzes the effects of governeent debt and income taxes on consumption and saving in a world of infinitely-lived households having uncertain and heterogeneous incomes. The special structure of the model allows exact aggregation across households despite incomplete mmrkets. The effects of government debt are shown to be substantial, roughly comparable to those resulting from finite horizons, and crucially dependent on the length of time until the debt is repaid. Also, anticipated changes in taxes are shown to cause anticipated changes in consumption. Finally, an index of fiscal stance is derived.